2004
DOI: 10.1038/sj.emboj.7600186
|View full text |Cite
|
Sign up to set email alerts
|

Cullin-based ubiquitin ligases: Cul3–BTB complexes join the family

Abstract: Cullin-based E3 ligases target substrates for ubiquitindependent degradation by the 26S proteasome. The SCF (Skp1-Cul1-F-box) and ECS (ElonginC-Cul2-SOCS box) complexes are so far the best-characterized cullin-based ligases. Their atomic structure has been solved recently, and several substrates have been described in different organisms. In addition to Cul1 and Cul2, higher eucaryotic genomes encode for three other cullins: Cul3, Cul4, and Cul5. Recent results have shed light on the molecular composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
256
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(262 citation statements)
references
References 45 publications
5
256
0
1
Order By: Relevance
“…1), which is predicted to interact with Cul3 (29)(30)(31). However, mutations in the BTB domain of human Keap1 at the predicted interface between BTB and Cul3 did not disrupt the Keap1-Cul3 interaction, but led to downregulation of Neh2 ubiquitination as well as up-regulation of Keap1 ubiquitination (21).…”
Section: Discussionmentioning
confidence: 99%
“…1), which is predicted to interact with Cul3 (29)(30)(31). However, mutations in the BTB domain of human Keap1 at the predicted interface between BTB and Cul3 did not disrupt the Keap1-Cul3 interaction, but led to downregulation of Neh2 ubiquitination as well as up-regulation of Keap1 ubiquitination (21).…”
Section: Discussionmentioning
confidence: 99%
“…Once bound to the F-box, the SCF substrate will be brought closer to the Cul1/Hrt1 catalytic core of this ubiquitin-ligase by Skp1. Finally, Cul1/Hrt1 will recruit the E2 enzyme, Cdc34, and will induce substrate ubiquitination (Pintard et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The latter may involve a number of different E3 ubiquitin ligases. One large family of E3 ubiquitin ligases consists of multisubunit protein complexes organized by the Cullin family of scaffolding proteins (27). Our study provides evidence for a role of Cul3-based E3 ubiquitin ligases in the regulation of Glis3 protein stability and a possible connection among the actions of Cul3, SUFU, and Glis3.…”
Section: Discussionmentioning
confidence: 65%
“…Our study provides evidence for a role of Cul3-based E3 ubiquitin ligases in the regulation of Glis3 protein stability and a possible connection among the actions of Cul3, SUFU, and Glis3. Cul3 typically promotes ubiquitin-dependent proteolytic degradation by binding to the BTB domain of adaptor proteins that target specific protein substrates (27); therefore, it is likely that association between Cul3 and Glis3 is mediated by a similar mechanism. We demonstrated that Cul3 is part of a Glis3 protein complex and is able to promote the polyubiquitination of Glis3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation